2017
DOI: 10.1007/978-3-319-54528-8_2-1
|View full text |Cite
|
Sign up to set email alerts
|

Inulin-Type Fructans Application in Gluten-Free Products: Functionality and Health Benefits

Abstract: The increasing demand on a high-quality gluten-free (GF) products and an increasing prevalence of GF consumers favors the development of research aimed to improve the overall quality of GF products. To obtain a functional GF product providing the additional health benefits, the fortification of GF food is applied. Recently, inulin-type fructans (ITFs) were proposed as multi-task ingredients of GF products, improving their nutritional and health-related properties. In this chapter, the most recent studies on GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 209 publications
(289 reference statements)
0
4
0
Order By: Relevance
“…Dietary fi bres consist of non-digestible carbohydrates and lignin that are intrinsic and intact in plants and should be resistant to the enzymes of the early-sections of the digestive tract and fermented in the colon by gut microbiota [Anderson et al, 2009]. The daily intake of dietary fi bre should range from 25 to 38 g [Drabińska et al, 2018a]. The Joint WHO/FAO Expert Consultation on Diet, Nutrition and the Prevention of Chronic Diseases [Nishida et al, 2004] stated that an adequate amount of fi bre in the diet confers several health benefi ts including body mass management, as well as reduction of hypertension and risk of type 2 diabetes and cardiovascular diseases [Anderson et al, 2009].…”
Section: Dietary Fi Brementioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fi bres consist of non-digestible carbohydrates and lignin that are intrinsic and intact in plants and should be resistant to the enzymes of the early-sections of the digestive tract and fermented in the colon by gut microbiota [Anderson et al, 2009]. The daily intake of dietary fi bre should range from 25 to 38 g [Drabińska et al, 2018a]. The Joint WHO/FAO Expert Consultation on Diet, Nutrition and the Prevention of Chronic Diseases [Nishida et al, 2004] stated that an adequate amount of fi bre in the diet confers several health benefi ts including body mass management, as well as reduction of hypertension and risk of type 2 diabetes and cardiovascular diseases [Anderson et al, 2009].…”
Section: Dietary Fi Brementioning
confidence: 99%
“…Inulin-type fructans (ITF) are commonly consumed soluble dietary fi bres, which are more fermentable and viscous than the insoluble fi bres [Slavin, 2013]. The structure of ITF, characterized by β-confi guration, determines their ability to reach the colon in the intact form and their prebiotic properties [Drabińska et al, 2018a]. ITF have not only nutritional quality, but can also affect the technological parameters of food products, which was widely studied in gluten-free breadmaking.…”
Section: Dietary Fi Brementioning
confidence: 99%
“…In the production of GF cakes and muffins, wheat flour has to be replaced with naturally GF flours, like rice flour (Marco & Rosell, ; Kringel et al ., ) or GF starches (Ronda & Roos, ). In comparison with conventional wheat bakery products, GF products are characterised by lower technological quality, in particular by crumbling texture, unattractive colour, faster staling (Gallagher et al ., ; Drabińska et al ., ), insufficient nutrients content (Saturni et al ., ; Matos Segura & Rosell, ) and poorer consumer acceptance (Drabińska et al ., ). Numerous studies demonstrated that both technological properties and nutritional value of GF products can be meaningfully improved by application of natural GF grains (Krupa‐Kozak et al ., ; Capriles & Arêas, ) or proteins of animal and vegetable origin (Nunes et al ., ; Krupa‐Kozak et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Inulin-type fructans (ITF) are water-soluble mixtures of oligo- or polysaccharides composed of β-D-fructosyl units linked by (2–1) glycosidic bonds [ 93 ]. Based on the degree of polymerization (DP), ITF can be further divided into long-chain inulin (DP > 10) and short-chain oligofructose, also called FOS (DP < 10) [ 94 ].…”
Section: Prebioticsmentioning
confidence: 99%